A rare case of sternal bony metastasis in hepatocellular carcinoma - Dhanju, Avtar Singh; Rajput, Smit (International Journal of Advances in Medicine, 2017)
Hepatocellular carcinoma (HCC) is one of the most common malignancies of the world and about 30-50% cases of HCC have extra hepatic metastases.1 Bone is considered to be an uncommon site for metastasis in HCC. We report a case of HCC with secondaries in the body of sternum. Review of literature also shows that bone is not that uncommon site for metastases in HCC and HCC should be considered in the differential diagnosis of patients with bony metastases.